Comparison of Intra Articular Platelet Rich Plasma with Corticosteroids in Patients with Temporomandibular Dysfunction - Sahar Usman; Sufyan Ahmed; Sana Iqbal; Mehwash Kashif; Mirza Hamid Baig; Ajeet Kumar; Uzma Shamsi (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2023)
Objective: To evaluate comparison of intra-articular injection of Platelet Rich Plasma (PRP) and corticosteroids in patients with Temporo Mandibular Joint Dysfunction syndrome.